SIMULASI OPERASI HARIAN WADUK SADAWARNA KABUPATEN SUBANG - Harunnrasyid
Absrtact: Sadawarna Reservoir is a reservoir to be built in Cipunegara River, and its to be located in Sadawarna Village, Subang Regency. The reservoir construction is considered to be important in order to fulfill the main water requirment of people especially in Subang, Sumedang and Indramayu Regency, which is increasing today. Referring to the previous studies, as a matter of fact Cipunegara River has quite big potensial of water. However, the water was just neglected in the rainy season and it was felt to be a crucial thing in the dry season. Therefore, one of the reservoir in Cipunegara River, exactly in Sadawarna Village, was planned to be built in order to fulfill the main water requirment of people in the service area. Besides, it is to be made as rainwater reservation that will gradually give a ground water potensial to some shallow wells, which can give a benefit to the surounding people. In order to analyze the compatibility between the needs and water availability in the reservoir from time to time, it has been conducted an analysis of daily operation of Sadawarna Reservoir. The analysis aims to identify water fluctuation and arrange the water needs in the reservoir from time to time or at least it can be used to irrigate the surrounding area all the year. The analysis of daily operation is based on the projection of water need planning in the service areas. The needs of water on the Sadawarna Reservoir includes : The needs for irrigation 29,220 Ha rice field, which is classified into four part area, on the left area, which is 13,149 Ha, divided into two part area and the right area, which is 16,071 Ha, divided into two part area, the need clean water for the people in Subang Regency about 326.08 lt/sec and Indramayu Regency about 155.43 lt/sec, the need for industries and commercials (Pertamina Industries, Ice factories, Hospitals and Hotels).The simulation of reservoir daily operation is a methode to identify the fluctuation of water in the reservoir from time to time. The simulation of daily operation of Sadawarna reservoir has been analyzed by using the data of daily rainfall from 1987 up to 2003 and the data of climate in Bandung from 1990 up to 1995 and from 1999 up to 2002. The basic principle of this simulation is the fixed amount of input water mass (inflow), output (outflow) and the storage in the reservoir. The input is the daily total discharge (Qin total) going into the reservoir from time to time (series). The output is the total water used, which is predicted from the projection of irrigation and non irrigation water need (such as clean water for the people, commercials, industries and maintenance flow) and the amount of water will spill when the elevation of water surface is over then + 78.5 m. The reservoir basis elevation is + 60 m and the spill elevation is + 78.5 m, so the analyzing of the reservoir volume is Qinput - Qoutput. However, if the water elevation in the reservoir is higher then the spillway elevation, there will be retention in the reservoir signed with the increasing of discharge in the form of run off discharge depending on the height of water surface on the spill. The analysis of daily operation of Sadawarna Reservoir is expected to be made as guidance in supplying the water requirment of the service area and a correction towards the needed reservoir water volume by seem the water requirment with the volume of the reservoir volume. By referring to that analysis, the failure and the success of the daily operation can be measured. A failure will occur if the water elevation in the reservoir in the reservoir reaches the lowest elevation, which is elevation + 60 m.